Shoulder Dislocations - V. B. Bondarev; A. Y. Vaza; A. M. Fayn; R. S. Titov (Неотложная медицинская помощь, 2020)
ABSTRACT. Shoulder dislocations are among the most common injuries and occupy the first place among all dislocations of limbs. Currently, the conventional approach to the treatment and diagnosis of this pathology is preserved. The closed reduction is performed under local anesthesia, the limb is immobilized with a bandage sling. There is no single opinion on the period of immobilization. Common indications for surgical treatment are unreduced, habitual and open shoulder dislocations. The preference is given to operations with the restoration of anatomy, while at the end of the last century, techniques were often used to limit the amplitude of movements in the shoulder joint. Currently unphysiological reconstruction methods are not favourable, since they violate the normal biomechanics of the shoulder joint and do not directly affect the pathological substrate of damage. Outcomes after arthroscopic options for operations are not inferior to those after open interventions. This article provides an overview of clinical and radiological methods for examining patients and treatment options for this pathology.